The amnesiac gene product is expressed in two neurons in the Drosophila brain that are critical for memory. - Waddell, S; Armstrong, J; Kitamoto, T; Kaiser, K; Quinn, W (2000)
Mutations in the amnesiac gene in Drosophila affect both memory retention and ethanol sensitivity. The predicted amnesiac gene product, AMN, is an apparent preproneuropeptide, and previous studies suggest that it stimulates cAMP synthesis. Here we show that, unlike other learning-related Drosophila proteins, AMN is not preferentially expressed in mushroom bodies. Instead, it is strongly expressed in two large neurons that project over all the lobes of the mushroom bodies, a finding that suggests a modulatory role for AMN in memory formation. Genetically engineered blockade of vesicle recycling in these cells abbreviates memory as in the amnesiac mutant. Moreover, restoration of amn gene expression to these cells reestablishes normal olfactory memory in an amn deletion background. These results indicate that AMN neuropeptide release onto the mushroom bodies is critical for normal olfactory memory.